Azithromycin Clears Bordetella pertussis Infection in Mice but Also Modulates Innate and Adaptive Immune Responses and T Cell Memory - Borkner, Lisa; Misiak, Alicja; Wilk, Mieszko M.; Mills, Kingston H. G. (Frontiers in Immunology, 2018)
Treatment with the macrolide antibiotic azithromycin (AZM) is an important intervention for controlling infection of children with Bordetella pertussis and as a prophylaxis for preventing transmission to family members. However, antibiotics are known to have immunomodulatory effects independent of their antimicrobial activity. Here, we used a mouse model to examine the effects of AZM treatment on clearance of B. pertussis and induction of innate and adaptive immunity. We found that treatment of mice with AZM either 7 or 14 days post challenge effectively cleared the bacteria from the lungs. The numbers of innate immune cells in the lungs were significantly reduced in antibiotic-treated mice. Furthermore, AZM reduced the activation status of macrophages and dendritic cells, but only in mice treated on day 7. Early treatment with antibiotics also reduced the frequency of tissue-resident T cells and IL-17-producing cells in the lungs. To assess the immunomodulatory effects of AZM independent of its antimicrobial activity, mice were antibiotic treated during immunization with a whole cell pertussis (wP) vaccine. Protection against B. pertussis induced by immunization with wP was slightly reduced in AZM-treated mice. Antibiotic-treated wP-immunized mice had reduced numbers of lung-resident memory CD4 T cells and IL-17-production and reduced CD49d expression on splenic CD4 T cells after challenge, suggestive of impaired CD4 T cell memory. Taken together these results suggest that AZM can modulate the induction of memory CD4 T cells during B. pertussis infection, but this may in part be due to the clearance of B. pertussis and resulting loss of components that stimulate innate and adaptive immune response.